PENGANTAR DARI EDITOR VOL. 16 NO. 1 (APRIL) 2026 - Surtiati, Rahayu (UI Scholars Hub, 2026)
This edition of Paradigma: Jurnal Kajian Budaya Vol. 16 No. 1 (2026) presents a range of studies that affirm culture as a dynamic domain continuously shaped by processes of negotiation, transformation, and reinterpretation across diverse social, historical, and political contexts. The articles explore the creation and innovation of artistic practices as representations of collective identity, the dialectics between preservation and renewal of tradition, and the strategic role of culture in national development. In addition, issues of historiography and colonial legacy are examined through postcolonial perspectives that offer new readings of Indonesian art, while discussions on values and social structures address leadership grounded in local wisdom alongside critiques of institutional responses to gender-based violence. Ethnographic and archaeological approaches further enrich this issue by highlighting cultural practices, spaces, and material heritage as parts of complex systems of meaning. Overall, this edition underscores the importance of cultural studies as a critical instrument for understanding the past, interpreting contemporary realities, and shaping a more inclusive and sustainable future.